Strategi Differentiation dalam Membangun Keunggulan Kompetitif Industri Battery Swapping Station: (Studi Kasus PT. XYZ) - Ahmad Mikhail Samudra Usman; Umanto Umanto (Journal of Creative Student Research, 2026)
The transition toward clean energy has accelerated the growth of the Electric Vehicle (EV) industry and increased the strategic importance of batteries within the future energy value chain. Although Indonesia possesses the world's largest nickel reserves, Vietnam and Thailand have emerged as leading EV and battery markets in the ASEAN region. This study aims to analyze the competitive differentiation strategies implemented by Vietnam and Thailand through the cases of VinFast and BYD. The research employs a post-positivist approach with a qualitative descriptive method. Data were collected through a literature review of academic journals, international organization reports, government documents, and industry publications related to EVs and battery development. The analysis utilizes Hambrick and Fredrickson’s Strategy Diamond, particularly the differentiators dimension, supported by SWOT analysis. Research findings indicate that the success of PT XYZ’s BSS is underpinned by high levels of trust and legitimacy, stemming from its status as a subsidiary of a state-owned enterprise (SOE) in the energy sector, combined with consistent product quality. These findings demonstrate that a strong foundation of corporate legitimacy, established through earlier ventures (even those outside the renewable energy sector), can significantly contribute to cultivating an audience that is familiar with and trusts the company’s product and service image.